The effect of stroboscopic visual training on eye-hand coordination - Ellison, P.; Jones, C.; Sparks, S. A.; Murphy, P. N.; Page, R. M.; Carnegie, E.; Marchant, D. C. (Sport Sciences for Health, 2020)
Background: Stroboscopic visual training (SVT) has been shown to improve cognitive skills and perceptual performance by carrying out events under situations of intermittent vision. Aims: The aim of this study was to investigate whether an SVT training period could improve the eye-hand coordination (EHC) performance on a practiced task for a group of sports participants. Methods: Sixty-two male participants were randomly assigned to either a strobe group (SG n = 31), or control group (CG n = 31). The method employed a Sport Vision Trainer™ 80 sensor pad to measure the mean speed of reaction time of participants extinguishing randomly illuminated lights on an electronic board. One trial consists of 20 lights. One week following pre-testing on the Sport Vision Trainer™ (4 × 6 trials), a pre-training baseline assessment of 1 × 6 trials was conducted to measure their abilities to complete the EHC task. Four × six trials (480 lights) were then completed in the training phase with the CG continuing to train with unimpaired vision, whilst the SG wore Nike Vapor Strobe® (controlled rate of 100 ms visible to 150 ms opaque). Post-training assessments were administered immediately, 10 min and 10 days after SVT each consisting of six trials (120 lights). A visual search (VS) non-trained transfer test was also administered pre-SVT and after 10 days. This involved an e-prime programme using a laptop where participants had to identify a target stimulus located amongst distractor stimuli. Results: Treatment effects were observed at each time point. Baseline performance was significantly related to retention performance immediately (p = .003), 10-min post (p = .001) and 10 days post-training (p = .002). No significant differences were found for the VS test. Conclusion: An acute SVT exposure using stroboscopic goggles significantly improved EHC performance. Future research should explore these mechanisms further using different exposure, frequencies, and focused identification of training drills as a complementary intervention for individual or team sports.